MEDIA AND STUDENTS: HOW DIFFERENT GENERATION OF CULINARY ART STUDENTS RESPONDS TO VIRTUAL SAFETY LABORATORY AS LEARNING MEDIA - Anggraeni Stj, Rr. Christiana Mayang; Pinandoyo, Dimas Bayu (P3M Politeknik Negeri Media Kreatif, 2024)
Virtual laboratories are the latest learning media developed to support student learning. But unfortunately, data regarding its acceptance is not yet available. This research aims to examine how culinary arts students from different classes respond to the food safety virtual laboratory as a learning medium. Method used was a questionnaire using a level 5 Likert scale. Data collected was analyzed with the Single Tail T Test using Excel program. Student responses analyzed were in the form of readability, visual appearance, comfort, and material taught through learning media. From the analysis carried out, it is known that all students gave positive response to virtual food safety laboratory as a learning medium. It was found that early generation students responded much better with a score of 4.25±0.66 compared to final generation students with a score of 4.00±0.00 out of 5.00. Generation significantly influences students' responses to virtual laboratories as a learning medium.